How to Burst into Contemporaneity? - V. I. Zagvyazinsky (Образование и наука)
The paper, written by V. I. Zagvyazinsky, academician and Chief Editor of «Education and Science» journal, is a comment on the previous issue’s publication of «Pedagogy in the Era of Non-Classical Science» by V. L. Benin. The author continues the discussion about the low quality pedagogic research of the recent years. Among the main reasons for insufficient research level, it is emphasized that young scientists are not quite ready for entering the socio-cultural reality because of their methodological illiteracy and non-compliance with the principles declared by the researchers themselves – i.e. systematism, competence, social and personal orientation, cultural conformity, activity approach, value-semantic orientation of education, foot-hold on the internal mechanisms, variability, dialogism, pedagogic cooperation, etc. The author criticizes the latest trends of so called «breaking into contemporaneity» by pedagogical science - the poly-paradigmatic idea as a new methodological basis of pedagogy; and synergetics as a general pedagogical methodology. Free paradigm constructing by the authors brought about the unreasonable methodological pluralism; whereas the failure of synergetics as methodological basis of pedagogy is related to its incompatibility with the person-oriented individual approach to personality formation. To get rid of the existing shortcomings of pedagogic research the author recommends to organize methodological training courses, schools, seminars, workshops, internship in the scientifically advanced centers that already have postgraduate and doctorate courses along with the fundamental scientific schools.